Posicionamentos de adolescentes sobre enunciados de conformação corporal que circulam no Instagram - Lima, Juliana Meirelles de (2020)
In this thesis, we will argue that the proposed concept of body conformation is established in the relationship between health prescriptions and normative body prescriptions. We assume that the association between thinness and health is a social construct and that the Instagram platform is the scene of a wide negotiation of meanings on the subject. We began the work with a review of the biomedical literature on the issue of body weight. From this study, we discuss the construction of overweight as a social problem. We continue with the analysis of daily body monitoring practices. We understand the prescriptive discourses of body aesthetics as dynamic constructions and situated in a social context. We consider the intersection of gender with body conformation a feminist issue. In this context, we evaluate how the notion of femininity is intertwined with normatizations of body shapes and sizes. In view of the circulation of prescriptive health and aesthetic content, we chose the Instagram as base for the structuring and operationalization of workshops conducted with groups of adolescents. We characterize the uses of this tool and find that the female gender is more active in their interaction. In the workshops, we foster, from Instagram images, discussions about the adolescents’ positions regarding statements of body conformation based on the themes health, weight, body and healthy eating. We built dialogical maps to understand the discursive dynamics of the 6 workshops held. In this scenario, we developed a fruitful space for reflection and co-construction of meanings in relation to body conformation prescriptions. Adolescents, in general, did not position themselves as passive recipients of these statements, although they do not disregard their effects. Their discourses on body conformation dialogically produced in the group reveal possibilities of deconstruction of these normative prescriptions. Finally, we consider that these adolescents still subvert Instagram not only as a vehicle for the circulation of standards, but also as a diffuser of discourses that express body diversity movements. Thus, the results give us clues as to how the adolescents in this research interact with these patterns, questioning them, recognizing themselves or not, and assuming them or not